The Two Triclinia of Pope Leo III as “Icons of Power” - Curzi, Gaetano (IKON, 2016)
Abstract Pope Leo III (795-816) built two monumental representative rooms for banquets, court hearings and ceremonies in the Lateran. These, called triclinia, were inspired by ancient and byzantine models, rich in imperial symbolism. The interiors of these buildings were decorated with marbles, paintings and, above all, mosaics in the main apses. The first celebrated the role of the pope as successor of Peter, vicar of Christ and medium for the transmission of the secular power from Constantine to Charlemagne. In the latter, the pope was usually represented taking part in a banquet with eleven diners in the central apse, where Christ, Peter and Paul were depicted, so that the pope becomes part of the group of the apostles, whose stories were represented on the walls. These magnificent buildings are unfortunately destroyed, so this paper offers a reinterpretation of these monuments by reviewing the literary and figurative evidences and taking new elements into account. It reveals that the choice of architectural models and iconographic programs was designed to build an iconic image of the papacy which emphasized the legacy of the ancient word, the pope’s role as an intermediary with Christ and his leadership over the temporal power.